Common variants near ATM are associated with glycemic response to metformin in type 2 diabetes - CORVIN, AIDEN PETER (My University, 2011)
Metformin is the most commonly used pharmacological therapy for type 2 diabetes. We carried out a GWA study on glycaemic response to metformin in 1024 Scottish patients with type 2 diabetes. Replication was in two cohorts consisting of 1783 Scottish patients and 1113 patients from the UK Prospective Diabetes Study. In a meta-analysis (n=3920) we observed an association (P=2.9 *10 ?9 ) for a SNP rs11212617 at a locus containing the ataxia telangiectasia mutated ( ATM ) gene with an odds ratio of 1.35 (95% CI 1.22 to 1.49) for treatment success. In a rat hepatoma cell line, inhibition of ATM with KU-55933 attenuated the phosphorylation and activation of AMPK in response to metformin. We conclude that ATM, a gene known to beinvolved in DNA repair and cell cycle control, plays a role in the effect of metformin upstream of AMPK, and variation in this gene alters glycaemic response to metformin
PUBLISHED
PubMed ID: 21186350
Keywords: glycaemic respons; glycaemic respons